More than 5000 patients with metastatic melanoma in Europe per year do not have access to recommended first-line innovative treatments. (April 2017) - Kandolf Sekulovic, L.; Peris, K.; Hauschild, A.; Stratigos, A.; Grob, J.-J.; Nathan, P.; Dummer, R.; Forsea, A.-M.; Hoeller, C.; Gogas, H.; Demidov, L.; Lebbe, C.; et al.
Abstract: Background: Despite the efficacy of innovative treatments for metastatic melanoma, their high costs has led to disparities in cancer care among different European countries. We analysed the availability of these innovative therapies in Europe and estimated the number of patients without access to first-line recommended treatment per current guidelines of professional entities such as the European Society for Medical Oncology (ESMO), the European Organisation for Research and Treatment of Cancer (EORTC), the European Association of Dermato-Oncology (EADO), and European Dermatology Forum (EDF). Materials and methods: Web-based online survey was conducted in 30 European countries with questions about the treatment schedules from 1st May 2015 to 1st May 2016: number of metastatic melanoma patients, registration and reimbursement of innovative medicines (updated data, as of 1st October 2016), percentage of patients treated and availability of clinical studies and compassionate-use programmes. Results: The recommended BRAF inhibitor (BRAFi) + MEK inhibitor (MEKi) combination was both registered and fully reimbursed in 9/30 (30%) countries, and in 13/30 (43%) (all from Eastern Europe) not reimbursed. First-line immunotherapy with anti-PD1 antibodies was registered and fully reimbursed in 14/30 (47%) countries, while in 13/30 (43%) (all from Eastern Europe) not reimbursed. It was estimated that in Europe 19, 600 patients with metastatic melanoma are treated, and 5238 (27%) do not have access to recommended first-line therapy. Significant correlation was found between human development index (HDI, UNDP report 2015), (r = 0.662; p < 0.001), health expenditure per capita (r = 0.695; p < 0.001) and the Mackenbach score of health policy performance (r = 0.765; p < 0.001) with the percentage of patients treated with innovative medicines and a number of reimbursed medicines. Conclusions: Great discrepancy exists in metastatic melanoma treatment across Europe. It is crucial to increase the awareness of national and European policymakers, oncological societies, melanoma patients' associations and pharma industry. Highlights: New innovative therapies improve dramatically the prognosis of metastatic melanoma and are becoming standard of care. Large disparities in access exist in Europe with over 5000 patients annually denied life-saving treatments, mostly in Eastern European countries. Innovative procedures for affordable and equitable care must be urgently found.